Comparative study of immobilized enzyme on nano-composite (SCN) and free enzyme of invertase isolated from baker's yeast - Chouia, Maroua; Derouiche, Samir (Future Science, 2025)
The objective of this study was to compare the properties and performance of invertase enzyme isolated from baker's yeast, both in free and immobilized form on a starch-copper nanocomposite (SCN). The SCN was synthesized using starch as a reducing agent for the biological production of copper nanoparticles (CuNPs). The Characterization of SCN was performed using Fourier transform infrared (FT-IR) spectroscopy, scanning electron microscopy (SEM), and X-ray diffraction to confirm nanoparticle formation and structural properties. The immobilization of invertase onto SCN was optimized by varying nanoparticle concentration, pH, incubation time, and temperature to maximize enzyme attachment and activity. Enzyme activity was measured for both free and immobilized forms to determine the immobilization efficiency. The study found that the high levels of enzyme immobilization were observed at pH = 9, temperature T = 30, and 3% SCN concentration. For both free and immobilized invertase, the ideal reaction temperatures were 35°C and 40°C, with corresponding pH values of 5 and 4.5. Reusability experiments revealed that the immobilized enzyme retained 49% of its activity after ten cycles, demonstrating improved stability and potential for repeated use. The results suggest that enzyme immobilization on SCN occurs through non-covalent interactions, providing a practical and sustainable approach for biocatalytic applications. This research highlights the potential of starch-based nanocomposites for enzyme stabilization, offering a cost-effective and environmentally friendly solution for industrial and biotechnological applications.